2020
DOI: 10.1016/j.jhsg.2020.08.006
|View full text |Cite|
|
Sign up to set email alerts
|

Ochrobactrum anthropi Infection of the Hand

Abstract: Ochrobactrum anthropi is an opportunistic, low-virulence pathogen occasionally associated with human infections and found largely in immunocompromised patients and those with intravascular devices. We report the case of a healthy 70-year-old man who presented with an infection of the hand, who had no history of trauma but had been gardening for 4 months. Despite surgical debridement and empirical antibiotics, the infection could not be controlled. Cultures revealed O anthropi. Antibiotic treatment was adapted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“… 24 It is usually an opportunistic, low‐virulence pathogen occasionally associated with human infections and reported commonly with immunocompromised patients or patients with intravascular devices. 25 Cases associated with indwelling vascular catheters, Gullain–Barre syndrome, neonatal sepsis with prematurity, meningitis from nosocomial infections and pneumonia have been described. 2 , 23 , 26 , 27 , 28 Antibiotic susceptibility varies, but it is generally susceptible to co‐trimoxazole, quinolones, and aminoglycosides, particularly gentamicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 It is usually an opportunistic, low‐virulence pathogen occasionally associated with human infections and reported commonly with immunocompromised patients or patients with intravascular devices. 25 Cases associated with indwelling vascular catheters, Gullain–Barre syndrome, neonatal sepsis with prematurity, meningitis from nosocomial infections and pneumonia have been described. 2 , 23 , 26 , 27 , 28 Antibiotic susceptibility varies, but it is generally susceptible to co‐trimoxazole, quinolones, and aminoglycosides, particularly gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be part of the normal gastrointestinal tract flora 24 . It is usually an opportunistic, low‐virulence pathogen occasionally associated with human infections and reported commonly with immunocompromised patients or patients with intravascular devices 25 . Cases associated with indwelling vascular catheters, Gullain–Barre syndrome, neonatal sepsis with prematurity, meningitis from nosocomial infections and pneumonia have been described 2,23,26–28 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the culture-dependent method revealed that the abundance of many opportunistic pathogens and drug-resistant bacteria was significantly higher in the xylem of the diseased samples compared to their healthy counterparts. Infections in humans have been reported mostly with opportunistic pathogens, including Achromobacter ( Menetrey et al., 2021 ), Acinetobacter ( Amorim and Nascimento, 2017 ) , Brucella ( Roop et al., 2021 ), Delftia ( Deb et al., 2020 ), Escherichia ( Bhatt et al., 2019 ), Herbaspirillum ( Bloise et al., 2021 ), Klebsiella ( Rodríguez–Medina et al., 2019 ), Ochrobactrum ( Bratschi et al., 2020 ), Pantoea ( Cobo et al., 2021 ), Ralstonia ( Ryan and Adley, 2014 ) and Stenotrophomonas ( Menetrey et al., 2021 ). Moreover, Acinetobacter ( Shin et al., 2020 ), Escherichia ( Tang et al., 2022 ), Klebsiella ( Dong et al., 2022 ), Pantoea ( Yoshimura et al., 2022 ) and Stenotrophomonas ( Ferreira et al., 2020 ) have been shown to have multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%